Analisis Elastisitas Harga dan Pendapatan dalam Perspektif Ekonomi Konvensional dan Mikro Islam - Zohya Azzura; Eka Christina Waruwu; Reni Ria Armayani Hasibuan (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2025)
This study aims to analyze price elasticity and income elasticity of products by integrating perspectives from conventional economics and Islamic microeconomics. In conventional economics, price and income elasticity are used to understand consumer demand sensitivity to changes in price and income. Meanwhile, Islamic microeconomics adds an ethical dimension, such as the prohibition of israf (wastefulness) and the importance of balanced consumption. The findings indicate that elasticity analysis is crucial not only for business strategies and economic policies but also must incorporate Islamic economic principles to promote sustainable and ethical consumption. This study suggests that integrating Islamic microeconomic values in elasticity analysis can enrich the understanding of consumer behavior and foster more inclusive economic policies.